Transforming Legal Scholarship: Strategic and Innovative Approaches to Developing a Student Edited Law Journal Toward International Recognition - Arifin, Ridwan; Alkadri, Riska; Irawaty; Baiquni, Muhammad Iqbal (LITIGASI, 2024)
The transformation of legal scholarship in higher education increasingly depends on the capacity of student-edited law journals to align with international standards of academic quality, editorial integrity, and global visibility. In Indonesia, several student-run law journals—such as those managed by Universitas Negeri Semarang (UNNES), Universitas Gadjah Mada, and Universitas Indonesia—have begun experimenting with digital platforms, peer review systems, and open-access dissemination to enhance their academic standing. Building upon previous research adopting and modifying the Harvard Law Review model of editorial management, this study explores strategic and innovative approaches to developing student-edited law journals toward international recognition. Using a qualitative and comparative descriptive method, it analyzes the transformation of editorial practices, digitalization processes, peer review mechanisms, and collaborative initiatives across selected Indonesian law faculties. The findings indicate that sustainable transformation requires a holistic strategy integrating academic rigor, technological innovation, and strong institutional support. Moreover, international benchmarking, ethical publication standards, and cross-border academic partnerships are identified as crucial factors in improving journal reputation and visibility. This study contributes to the advancement of legal scholarship in Indonesia by proposing a practical framework that can guide student-edited law journals—particularly at UNNES—in evolving from local academic initiatives into internationally reputable platforms for legal research and discourse.